Adaptation styles in web-based learning: a case study on TESL undergraduates of UNIMAS - Khairunnisa, Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2002)
This case study is a replication of a study done by Lee (2001) entitled "Profiling students' adaptation styles in Web-based learning" in Korean universities. The main objective of this study is to identify UNIMAS TESL undergraduates' adaptation styles in web-based learning environment. This study is aimed to investigate if the perceptions of undergraduates influence their academic achievement. It also aimed to identify the undergraduates' learning preference in the web-based learning environment. A total of 100 respondents which comprised of first, second and third year TESL undergraduates were involved in this study. The instruments used in the data collection. in this study were questionnaire and structured interview. The questionnaire was adapted from. Web Experience/Perception of Web Language Learning Environment by Uschi Felix (1998) and Evaluation of Web-Based Leaming program by Gregor Kennedy (1998). The data gathered were analyzed using descriptive and inferential statistics. Pearson correlation was used to determine if there is any correlation between perception of achievement and perception of the course. The findings of this study indicated that there were four distinct adaptation styles existed in UNIMAS TESL undergraduates in web-based instruction. There were weak correlations between the perception of achievement and the perception of the course. The UNIMAS TESL undergraduates also prefer to work alone, in pair and in group. As a whole, UNIMAS TESL undergraduates perceived the usefulness of web-based instruction. The results from the study could increase educators' understanding of the learners' adaptation styles in the web-based learning environment and used it to draw useful strategies for implementing and designing web-based instruction.The implications of the study and recommendations for future studies were also forwarded in this study.